PENGARUH TERPAAN PENGGUNAAN TAGAR #VILLAGESNOTFACTORIES TERHADAP CITRA MEREK PAKAIAN BERKELANJUTAN SUKKHACITTA (Survei pada Followers Akun Instagram @sukkhacitta) - Marlin Merliana (2023)
The utilization of social media also the use and optimization of social media features such as hashtags in an era of increasingly competitive business competition can be one of the strategies to build a brand through the formation of a positive brand image. This study aims to determine how much influence the exposure of hashtags usage has on the brand image of sustainable clothing by using the Uses and Effect theory as the main theoretical basis. This theory explains the relationship between communication delivered through social media could create an effect for media users. The information behind the hashtags usage that carried out through Instagram social media provides a level and makes audiences grow their perceptions of a brand, one of which is the formation of a brand image. The withdrawal of samples from the research population using non-probability sampling with purposive sampling method resulted in 100 samples. The data obtained is then processed using the correlation test, simple linear regression test, coefficient of determination test, and hypothesis testing. The results showed that there is a significant relationship between the exposure of #VillagesNotfactories hashtag usage and Sukkhcitta Sustainable Clothing Brand Image. The coefficient of determination obtained shows that there is an influence of 45.8% from the exposure of #VillagesNotfactories hashtags usage on Sukkhcitta's brand image. The results of hypothesis testing show that Ho is rejected and Ha is accepted, which means that there is a significant effect of exposure to the use of the hashtag #VillagesNotFactories on the Instagram account @sukkhacitta on the SukkhaCitta sustainable clothing brand image based on a survey of @sukkhacitta Instagram account's followers.